2022
DOI: 10.1002/bab.2314
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of superoxide dismutase by TAT and abalone peptides for the protection of skin cells against oxidative stress

Abstract: Trichoderma reesei superoxide dismutase (TrSOD) is a well-characterized enzyme being stable between 30 and 90 • C for 1 h with activity at pH between 2.6 and 9.0. This work aimed to clone, express, purify, and evaluate the protective effect antioxidant of this enzyme on skin cells when fused to transactivator of transcription (TAT) protein transduction domain of HIV-1 and abalone (Ab) peptides to allow cell penetration. TrSOD, TAT-TrSOD-Yfp (fused to yellow fluorescent protein), and Ab-TrSOD were expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…In vitro toxicity: Vaccine cytotoxicity was evaluated according to [19]. Briefly, 3T3 fibroblasts, CALU-3 lung cells, primary human fibroblasts (HLF), and rat lung cells (pneumocytes) were added to flat-bottom 96-well plates (Corning, Salt Lake City, UT, USA) at a concentration of 8000 cells per well.…”
Section: Toxicity Of Vaccine Formulationmentioning
confidence: 99%
“…In vitro toxicity: Vaccine cytotoxicity was evaluated according to [19]. Briefly, 3T3 fibroblasts, CALU-3 lung cells, primary human fibroblasts (HLF), and rat lung cells (pneumocytes) were added to flat-bottom 96-well plates (Corning, Salt Lake City, UT, USA) at a concentration of 8000 cells per well.…”
Section: Toxicity Of Vaccine Formulationmentioning
confidence: 99%
“…Marine fsh are very vulnerable in the early stage, and supplementation with antioxidants can strengthen the antioxidant system to resist oxidative injury such as DNA damage and lipid peroxidation [37,38]. SOD was involved in early-stage antioxidant defense, which refected the antioxidant status of animals [39]. Results showed that larvae fed TG and LG diets had signifcantly higher activities of SOD than the other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…CPPs typically contain more than five positively charged amino acids. Most cationic CPPs are derived from natural TAT (YGRKKRRQRRR) and penetratin (RQIKIWFQNRRMKWKK) peptides [53,66].…”
Section: Shuttle Peptides To Provide Neuroprotectionmentioning
confidence: 99%